Dinamika Pertumbuhan dan Perkembangan Kesehatan Masyarakat di Sumatera Timur, 1882-1942 - Nining Dia Ayu (Local History & Heritage, 2021)
This article discusses the growth and development of public health in East Sumatra in the period 1882-1942. Health is a study that continues to grow and the discussion about it never ends. The object of this discussion will focus on health problems in East Sumatra, which in the range of 1882-1942 opened access to plantations opened by one of the famous traders in the Netherlands. This is the background of various health problems experienced by people in East Sumatra. This paper is intended to summarize and explain specifically from the historical perspective and background of public health in East Sumatra in 1882-1942.